Partner supportive dyadic coping and relationship stability among parents of children with autism spectrum disorder - Löw, Ajana (Array, 2021)
Studies involving parents of children with autism spectrum disorder (ASD) have reported negative relationship outcomes for some couples and positive for others, indicating the need to determine the moderators of the link between stress and divorce. This study aims to examine the moderating effect of partner supportive dyadic coping, i.e., interpersonal coping that involves providing comfort, empathy, or practical advice to one’s partner, on the association between parental stress and relationship stability among parents of children with ASD. The study was conducted on a sample of parents (N=89) who met the criteria of being in a relationship and parenting at least one child diagnosed with ASD. The questionnaire included the Parental Stress Scale, a subscale of the Dyadic Coping Inventory, an item assessing the potential for divorce, and sociodemographic variables. The logistic regression analysis model explained a substantial amount of the variance of relationship stability. Higher probability of having a stable relationship was associated with lower levels of parental stress and higher levels of supportive dyadic coping. Additionally, supportive dyadic coping buffered the negative effect of parental stress: the effect of stress on relationship stability was evident only among participants whose partners showed low supportive dyadic coping. The results indicate that a relationship does not necessarily end in divorce when a couple experiences stressful circumstances, such as raising a child with ASD. The key factor could be supportive dyadic coping that prevents negative effects of stress on relationship maintenance. Support services should aim to enhance supportive dyadic coping skills among parents, and advocate for the fact that both stress and coping are joint processes of partners in a relationship.